BS EN IEC 61558-2-14. Safety of transformers, reactors, power supply units and combinations thereof. Part 2-14. Particular requirements and tests for variable transformers and power supply units incorporating variable transformers for general applications (30th April 2021) - British Standards Institution,
No abstract available